Biomorphic elements in the preservation of Sarawak Bidayuh cultural heritage interior (ARTEKS : Jurnal Teknik Arsitektur, 2025)
The Bidayuh community in Sarawak is known for its rich cultural heritage and traditional interior designs that reflect deep connections with nature. However, globalization and modernization pose significant threats to the preservation of these unique cultural elements. Traditional Bidayuh interiors are increasingly at risk of being overshadowed by contemporary designs that often neglect the cultural and aesthetic values inherent in biomorphic elements. This research identifies key biomorphic elements in traditional Bidayuh interiors, such as natural motifs, organic shapes, and traditional materials, and explores their integration into contemporary design to ensure cultural continuity. A qualitative research approach involves analyzing and find out the elements of Bidayuh cultural interior and develop aspect of biomorphic design through visual documentation and architectural analysis to provided guidelines for designers to sustain the legacy of Bidayuh cultural. The findings highlight the adaptability of biomorphic elements in modern interiors, demonstrating that traditional aesthetics can coexist with contemporary design without compromising cultural integrity. This culturally responsive approach fosters cultural pride and continuity among the Bidayuh people, offering a pathway to maintain their unique heritage amidst modern changes. The study provides a framework for designers and cultural practitioners to collaborate in preserving the Bidayuh cultural legacy for future generations.
Keywords: Bidayuh cultural; Biomorphic elements; Heritage; Interior; Preservation